The impact of a training program on the organizational climate of a public management institution assigned to the Ministry of Justice in Peru (Gestionar: revista de empresa y gobierno, 2022)
The purpose of this research is to study the state of the organizational climate in an institution attached to the Ministry of Justice in the department of Arequipa, Peru, to train personnel in topics related to improving the organizational climate and to evaluate the workers after the training sessions, using a control group and an experimental group, which will be matched in terms of age, sex, occupational group, length of service and working conditions. An adequate training program was developed for the type of institution, taking into account that the main activity is public service, which has been carried out in five four-hour sessions, with a didactic method based on group activities and games, with the active participation of the participants. The Sonia Palma Carrillo test was applied as an instrument, the same that was applied both in the pretest and posttest, obtaining different results in the experimental group, which have been measured statistically with different tests according to the type of comparison made in each one of them.
Keywords: training; organizational climate; management skills